Effects of Weed on Growth of Several Soybean Cultivar - Doni Hariandi; Didik Indradewa; Prapto Yudono (Gontor AGROTECH Science Journal, 2019)
Soybean is one of the food commodities, which contains vegetable protein, carbohydrates and fat, hence it is necessary to complement the nutrition. Demand consumption of soybean higher with increasing population annually, the production of soybean is still sufficient to complete the increasing of demand. Therefore, the increasing of soybean production has to be considered to decrease the dependency on imported. Soybean production can be increased by the cultivation technique. In this method, the present of weed should be concerned. Weed can reduce the quality and quantity of soybean. The research was done at Kebun Pendidikan, Penelitian dan Pengembangan Pertanian (KP4) Gadjah Mada University which located at Kalitirto, Berbah, Sleman, Yogyakarta, Indonesia. This research started on November 2015-April 2016. The research aims to identify the effects of weed on the growth analysis of several soybean cultivar. This field research is arranged using spit plot with three blocks as the repetition where the main-plot is the weed treatments andthose are weed-free, weeding in a critical period, and weedy. Sub plot is the soybean cultivars which are Anjasmoro, Argomulyo, Burangrang, Gema, Gepak Kuning, Kaba, and Wilis. The research’s result show the weed treatments would effect no significant difference in the leaf area index, net assimilation rate, crop growth rate (3 to 6 weeks after planted/WAP), specific leaf weight, and leaf area ratio (3 WAP). Which affects are the crop growth rate (6 to 9 WAP) and leaf area ratio (6 and 9 WAP)